2023
DOI: 10.1021/acs.joc.3c00026
|View full text |Cite
|
Sign up to set email alerts
|

Aminoguanidine-Catalyzed Reductive Cyclization of o-Phenylenediamines with CO2 in the Presence of Triethoxysilane

Abstract: An inexpensive and efficient aminoguanidinecatalyzed reductive cyclization of o-phenylenediamines with CO 2 in the presence of triethoxysilane is described. Various functionalized benzimidazoles, benzoxazole, and benzothiazole were synthesized in high yields. Mechanistic studies indicate that formic acid as a cocatalyst promotes the cyclization reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…It was found that the aminoguanidine hydrochloride salt catalyst provided a 97% yield toward benzimidazole in the presence (EtO) 3 SiH under atmospheric CO 2 pressure at 100 °C for 6 h (Table , entry 5). Further substrate scope was also studied, which gave an efficient yield . Liu and co-workers synthesized benzimidazole via CO 2 fixation catalyzed by B­(C6F5) 3 .…”
Section: Current Status Of Co2 Fixation For the Synthesis Of Benzimid...mentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the aminoguanidine hydrochloride salt catalyst provided a 97% yield toward benzimidazole in the presence (EtO) 3 SiH under atmospheric CO 2 pressure at 100 °C for 6 h (Table , entry 5). Further substrate scope was also studied, which gave an efficient yield . Liu and co-workers synthesized benzimidazole via CO 2 fixation catalyzed by B­(C6F5) 3 .…”
Section: Current Status Of Co2 Fixation For the Synthesis Of Benzimid...mentioning
confidence: 99%
“…Further substrate scope was also studied, which gave an efficient yield. 217 Liu and co-workers synthesized benzimidazole via CO 2 fixation catalyzed by B(C6F5) 3 . With a catalyst loading of 5 mol % in the presence of the solvent (EtO) 3 SiH and DMF as a base at 120 °C and a CO 2 pressure of 1 bar for 24 h, an excellent yield of 99% was achieved with a conversion of >99% (Table 1, entry 6).…”
Section: Introductionmentioning
confidence: 99%
“…Heterocyclic compounds play an essential role in the development of contemporary materials science, the pharmaceutical industry, synthetic organic chemistry, and so on. , For example, benzimidazoles and their derivatives emerged as a very important class of N-heterocyclic systems due to their remarkable biological characteristics of anticonvulsant, anti-inflammatory, antiallergic, antipyretic, antidepressive, and others. It has been also found in several common drugs, such as omeprazole, maribavir, bendamustine, nocodazole, Albendazole, Mebendazole, and so on. In this sense, the synthesis of benzimidazole is quite important for the current time attributing its increasing applications to the development medicinal field. However, the synthesis of benzimidazole has faced some problems, such as low yields, more byproducts, harsh reaction conditions, and so on. ,, Therefore, it is still necessary to develop catalytic systems for the construction of benzimidazole with the advantages of simple operation, catalyst recyclability, and high yield.…”
Section: Introductionmentioning
confidence: 99%